Development, Optimization and Evaluation of 2-Methoxy-Estradiol Loaded Nanocarrier for Prostate Cancer - Alhakamy, Nabil A.; Ahmed, Osama A.; Fahmy, Usama A.; Asfour, Hani Z.; Alghaith, Adel F.; Mahdi, Wael A.; Alshehri, Sultan; Md, Shadab (Frontiers in Pharmacology, 2021)
The therapeutic efficacy of antineoplastic agents possessing a selective target to the nucleus of the cancer cells could be enhanced through novel formulation approaches. Thus, towards the improvement of the anticancer potential of 2-methoxy estradiol (2ME) on prostate cancer, the drug was entrapped into the hydrophobic micelle core formulated with Phospholipon 90G and d-α-tocopheryl polyethylene glycol succinate (TPGS). Optimization of the formulation was done by Box-Behnken statistical design using Statgraphics software to standardize percentages of TPGS and phospholipid to obtain the smallest particle size. The optimized formulation was found to be spherical with nanometer size of 152 ± 5.2 nm, and low PDI (0.234). The entrapment efficiency of the micelle was 88.67 ± 3.21% with >93% release of 2ME within 24 h. There was a 16-fold increase in apoptosis and an 8-fold increase in necrosis of the PC-3 cells when incubated with 2ME micellar delivery compared to control cells (2.8 ± 0.2%). This increased apoptosis was further correlated with increased BAX expression (11.6 ± 0.7) and decreased BCL-2 expression (0.29 ± 0.05) in 2ME micelle treated cells when compared to the control group. Further, loss of mitochondrial membrane potential (⁓50-fold) by the drug-loaded micelle and free drug compared to control cells was found to be due to the generation of ROS. Findings on cell cycle analysis revealed the significant arrest of the G2-M phase of the PC-3 cells when incubated with the optimized formulation. Simultaneously, a significantly increased number of cells in pre-G1 revealed the maximum apoptotic potential of the drug when delivered via micellar formulation. Finally, upregulation of caspase-9, p53, and NO, with downregulation of TNF-α, NF-κβ, and inflammatory mediators of the PC-3 cells established the superiority of the micellar approach against prostate cancer. In summary, the acquired results highlighted the potentiality of the 2ME-micellar delivery tool for controlling the growth of prostate cancer cells for improved efficacy.